A reappraisal of 'analgesic hip'. Issue 4 (April 1986) - Doherty, M; Holt, M; MacMillan, P; Watt, I; Dieppe, P
Abstract : Nineteen patients with hip radiographs typical of 'analgesic hip' (rapidly destructive, atrophic arthropathy involving both femoral and acetabular components) have been studied. Women predominated (14:5), and all were elderly (mean age 74 years, range 64-83 years). Destructive hip disease was unilateral in all but one case. The mean interval from symptom onset to typical x ray appearance was short (one year, range three to 24 months), and persistent pain unresponsive to drug therapy was characteristic. Screening showed no metabolic or neurological disease. Contrary to previous reports, non-steroidal anti-inflammatory drugs could not be incriminated in development of the disease. Clinical and radiographic similarity to apatite associated destructive arthritis of other large joints was striking, and occurrence of the latter, uncommon condition in five patients (five shoulders, two knees) suggests that both descriptions represent a common articular response at different joint sites.